PENGARUH STRATEGI INFLUENCER MARKETING TERHADAP KEPUTUSAN PEMBELIAN PRODUK SKINCARE SKINTIFIC DI PLATFORM E-COMMERCE - Alfina Damayanti; Fia Amalia; Pupung Purnamasari (Samudra Publisher, 2025)
This study aims to analyze the impact of Influencer marketing strategies on purchasing decisions for the skintific skincare brand on e-commerce platforms. Influencer marketing has become one of the most effective marketing tactics in the digital era, especially in the beauty industry. This research employs a quantitative approach by distributing questionnaires to 100 respondents who are active skintific consumers on e-commerce platforms. The variables analyzed include influencer credibility, content appeal, and the relevance of the promoted product. The results show that influencer credibility significantly influences purchasing decisions, followed by content appeal, which effectively enhances consumer interest in trying the product. The relevance between the influencer and the product also plays an essential role in building consumer trust. These findings illustrate that the success of Influencer marketing strategies is not solely determined by the influencer’s popularity but also by their alignment with the target audience and the quality of the content delivered. This study is expected to serve as a reference for business practitioners to optimize marketing strategies through influencers to increase product sales.